Influence of light energy density on heat generation during photoactivation of dental composites with different dentin and composite thickness - Ricardo Danil Guiraldo; Simonides Consani; Aline Simprine de Souza; Rafael Leonardo Xediek Consani; Mario Alexandre Coelho Sinhoreti; Lourenço Correr-Sobrinho (University of São Paulo, 2009)
OBJECTIVE: The aim of this study was to determine the influence of different energy densities on the heat generated during photoactivation of Filtek Z250 (3M/ESPE) and Z100 (3M/ESPE) composite resins with different dentin and composite thickness. MATERIAL AND METHODS: The temperature increase was registered with a type-K thermocouple connected to a digital thermometer (Iopetherm 46). A chemically polymerized acrylic resin base was prepared to serve as a guide for the thermocouple and as a support for 0.5-, 1.0-, and 1.5-mm-thick bovine dentin discs. Circular elastomer molds (1.0 mm-height x 3.0-mm diameter or 2.0-mm height x 3.0-mm diameter) were adapted on the acrylic resin base to standardize the composite resin thickness. A conventional halogen light-curing unit (XL 2500, 3M/ESPE) was used with light intensity of 700 mW/cm². Energy density was calculated by the light intensity applied during a certain time with values of 28 J/cm² for Z100 and 14 J/cm² for Filtek Z250. The temperature change data were subjected to three-way ANOVA and Tukey's test at 5% level. RESULTS: The higher energy density (Z100) promoted greater temperature increase (p<0.05) than the lower energy density (Filtek Z250). For both composites and all composite thicknesses, the lowest dentin thickness (0.5 mm) yielded significantly higher (p<0.05) temperature increase than the other two dentin thicknesses. The 1-mm-thick composite resin layer yielded significantly higher (p<0.05) temperature changes for both composites and all dentin thicknesses. CONCLUSIONS: Temperature increase was influenced by higher energy density and dentin/composite thickness.